Football Viewers’ Perception of In-Game Commercials: A Study of Selected Football Viewing Centres in Kano Metropolis - Alamin Musa Muhammad (Darul Yasin Al Sys, 2026)
Television networks depend heavily on advertising revenue, yet the placement of in-game commercials during football matches often disrupts the viewing experience and provokes negative audience reactions. This study investigates football viewers’ attitudes, perceptions, and retention of in-game commercials across selected viewing centers in Kano metropolis, Nigeria, anchored in expectancy–value theory. The research adopts a descriptive survey design with a sample of 269 respondents proportionally drawn from a population of 900 viewers. Data were collected through structured questionnaires and analyzed using descriptive statistics. The findings reveal low exposure to and weak recall of halftime and floating commercials, with the majority of viewers perceiving advertisements as excessive, intrusive, and irritating. Only a minority of respondents reported purchasing advertised products, indicating limited influence of in-game commercials on consumer behavior. Although some viewers acknowledged the relevance of certain advertisements, overall attitudes were predominantly negative, manifested in frequent channel switching, disengagement, and expressions of manipulation. The study concludes that in-game commercials are largely ineffective in sustaining audience attention or driving consumer action and recommends that broadcasters and advertisers adopt less obtrusive, more engaging, and contextually relevant advertising strategies to enhance message retention and mitigate viewer dissatisfaction, thereby improving advertising effectiveness in sports broadcasting.